Instagram TV: Konvergensi Penyiaran Digital dan Media Sosial - Bianca Michelle Datubara; Irwansyah Irwansyah (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2019)
Along with the development of the internet, the existence of merger between one platform with another platform bring new features favored by the community, including the Social TV platform. Social TV presents an opportunity for the community to make privately owned TV channel that can be watched quickly and massively. Through content presented by social TV, the audience communicates directly while watching the social TV. One example of Social TV in Indonesia is Instagram TV. Instagram TV is a form of media convergence. Media convergence, however, was initiated and made possible by digital technology (Huang et al., 2006). The absence of regulations governing Social TV makes it seem as if the community can act freely in producing content on Instagram TV without regard to the impacts that will occur, such as comments that can be written freely, or the content produced. This study uses a text-based qualitative method with interviews as a data collection technique to show the phenomenon of Social TV IG TV being the impact of digital broadcasting. The results of this study are Instagram Tv is a clear example of the convergence of digital broadcasting and social media. One impact of the convergence of digital broadcasting and social media is the shift of viewers from conventional to digital. The impact of convergence needs to be monitored, one of the examples is with regulation.